Does the Sweating Severity of Primary Hyperhidrosis Sites Affect Post-Sympathotomy Results? - Çınar, Hüseyín Ulaş; Çelik, Burçin (The Thoracic and Cardiovascular Surgeon, 2020)
Background Improvement in quality of life (QOL) and patient satisfaction after endoscopic thoracic sympathotomy (ETS) in patients with primary hyperhidrosis may be affected by various factors. We examined whether the preoperative sweating severity of primary hyperhidrosis sites affects postoperative results.Methods The records of 112 patients who underwent bilateral ETS were reviewed retrospectively. The patients were divided into three groups according to the sweating severity score obtained from all primary hyperhidrosis sites (primary hyperhidrosis severity score [PHSS]) and analyzed comparatively. Group A (PHSS = 1–4) included 22 patients, Group B (PHSS = 5–8) 36 patients, and Group C (PHSS ≥ 9) 54 patients. Outcome measures included QOL prior to surgery, improvement in QOL after surgery, degree of clinical improvement, presence, severity, localization, and site number of reflex sweating (RS) and general patient satisfaction after 6 months of surgery.Results The preoperative QOL of patients with higher PHSS (groups B, C) was worse than other patients (group A). More than 91% of all patients had any level improvement in QOL, and over 96% had slight or great clinical improvement. RS developed in 80% of the patients, mostly in the back, very severe in 8%, and in median two different body areas. The overall patient satisfaction rate was more than 95%. There was no significant difference between the three groups in terms of all postoperative results.Conclusion Preoperative sweating severity of primary hyperhidrosis sites does not affect post-sympathotomy results. Surgeons should not be worried when deciding upon surgery, even in patients with high sweating severity.
Keywords: thoracoscopic sympathotomy; hyperhidrosis; nerve; quality of life; primary hyperhidrosis; reflex sweating